2008
DOI: 10.1152/ajpgi.00454.2007
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic receptors in gastrointestinal inflammation

Abstract: Purinergic receptors comprise a family of transmembrane receptors that are activated by extracellular nucleosides and nucleotides. The two major classes of purinergic receptors, P1 and P2, are expressed widely in the gastrointestinal tract as well as immune cells. The purinergic receptors serve a variety of functions from acting as neurotransmitters, to autocoid and paracrine signaling, to cell activation and immune response. Nucleosides and nucleotide agonist of purinergic receptors are released by many cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 135 publications
2
75
0
6
Order By: Relevance
“…It has become increasingly evident that extracellular purinergic signaling is disordered during disease and may play a role in pathogenesis (3,18). In the present study, we have identified an important role for ENTPD1 in defective vascular regulation during colitis.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…It has become increasingly evident that extracellular purinergic signaling is disordered during disease and may play a role in pathogenesis (3,18). In the present study, we have identified an important role for ENTPD1 in defective vascular regulation during colitis.…”
Section: Discussionmentioning
confidence: 51%
“…The RNA was reprecipitated using LiCl precipitation solution (Ambion). Subsequently, cDNA was reverse transcribed from 1 g of total RNA using SuperScript III (Invitrogen) and oligo(dT) [12][13][14][15][16][17][18] primers (Invitrogen). Real-time PCR was performed using the primers listed in Table 2 with a Roche Lightcycler and the Quantitech SYBR Green PCR kit (Qiagen).…”
Section: Animals and Materialsmentioning
confidence: 99%
“…A2bR is the only receptor expressed in epithelial cells of cecum and colon. A3R can be detected in jejunum and proximal colon [45,46] . Adenosine receptors are members of the G protein-coupled family of receptors [47] .…”
Section: Physiology Of Adenosine Metabolism By Intestinal Epithelium mentioning
confidence: 99%
“…It is reasonable then to suggest that these abnormalities in purinergic receptors or signaling pathways would have a significant impact on the overall behavior of the gut, enteric reflexes, and secretomotor behavior of the gut in bowel diseases. Purinergic receptors in gastrointestinal inflammation were the subject of a recent review by Kolachala et al [61]. A recent study by Guzman et al [45] using high-density oligonucleotide microarray analysis and SYBR-Green RT-PCR validation provided direct proof for differential dysregulation (upregulation or downregulation depending on the purine gene) of P2X 1 , P2X 2 , P2X 4 , P2X 7 , P2Y 1 , P2Y 2 , P2Y 4 , P2Y 6 , A 2a , A 2b , A 1 , or A 3 receptors in whole thickness gut specimens of experimental trinitrobenzene sulfonic acid (TNBS) colitis in rats .…”
Section: Differential Dysregulation Of Purinoceptors In Gi Disease Stmentioning
confidence: 99%